Poverty transitions in rural South West Nigeria (2012)
Poverty dynamics enables a better appreciation of the extent of poverty over time by distinguishing between households exiting and entering into poverty, those never poor and the persistently poor. However, it has not received much attention in the poverty literature in Nigeria, largely due to the lack of nationally representative panel data that track the poverty status of households over time. The dynamics of poverty in rural SouthWest Nigeria (SWN) was therefore investigated using regional panel data. Results showed that 49.5 percent of the households were non-poor while 28.2 percent were poor in both periods respectively. On the other hand, 22.3 percent of the households moved in and out of poverty between the two periods indicating a higher level of chronic poverty in rural South Western Nigeria. However, of the transient poor, while 6.8 percent exited poverty, a larger proportion (15.5 percent) moved into poverty. Results also revealed an overlap between the determinants of chronic and transient poverty as vulnerability aggravated both chronic and transient poverty in the region by increasing the odds of remaining and moving into poverty of poor and non poor households respectively. However, there were a few factors such as primary education of household head, membership of local group or association, access to remittance and credit associated with chronic but not transient poverty and vice versa. The study suggests adoption of mixed policies to poverty reduction and taking into account the factors that prevent the poor from slipping into poverty while giving due attention to the factors that help them overcome poverty in the targeting of the various anti-poverty programmes of government.